The Role Of Technology In Financial Sector Efficiency And Security - Nurhasiani, Pensi (Utami Publisher, 2025)
Digital transformation has become a primary driver of change in the global financial sector, including Indonesia. Deploying technologies such as electronic payment systems, artificial intelligence (AI), and blockchain not only accelerates financial services but also boosts operational efficiency and system security. This article analyses the contribution of digital technologies to cost efficiency and security enhancement in financial institutions through a literature review of scholarly works published between 2018 and 2025. Findings reveal that business-process automation enabled by business-intelligence tools and technology-based financial applications can cut operational costs by up to 30 percent. Meanwhile, encryption techniques and AI-powered fraud-detection systems reduce data breaches and fraudulent activities by approximately 25 percent. Furthermore, blockchain implementation provides transaction transparency and traceability, directly reinforcing customer trust. Consequently, digital technology adoption is not merely a catalyst for service transformation but also a critical strategy for competing in an increasingly dynamic digital economy. This study underscores the need for synergy among technological innovation, adaptive regulation, and improved digital literacy to create a financial system that is efficient, inclusive, and secure.